2010
DOI: 10.1111/j.1749-6632.2010.05784.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological modulation of vascular inflammation in atherothrombosis

Abstract: Vascular inflammation, especially at the level of endothelial cells, has been shown to play a pivotal role in the inception, progression, and clinical complications of atherosclerosis. The common denominators for the activation of inflammatory genes appear to be a small subset of transcription factors--among which include nuclear factor-κB, activator protein-1 (AP-1), and GATA--that function as the central hub of vascular inflammation. Strategies directed to inhibit both the secondary mediators and the primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 77 publications
1
17
0
Order By: Relevance
“…Atherosclerosis is a complex mechanism that involves inflammatory processes, especially at the level of endothelial cells [37,38]. Several potential inflammatory biomarkers for the prediction of atherosclerosis have been proposed including CRP, IL-6, TNF-α, SELL, SELP, VCAM-1, ICAM-1 [39][40][41].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Atherosclerosis is a complex mechanism that involves inflammatory processes, especially at the level of endothelial cells [37,38]. Several potential inflammatory biomarkers for the prediction of atherosclerosis have been proposed including CRP, IL-6, TNF-α, SELL, SELP, VCAM-1, ICAM-1 [39][40][41].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…AP-1 plays an important role in endothelial inflammation by activating the expression of proinflammatory cytokines and other proteins relevant to vascular pathology, such as selectins and monocyte chemoattractant protein-1 45,46) . Several studies have demonstrated that the NF-ELAM-1 site activated by proinflammatory cytokines is recognized by AP-1 and not by the CRE-binding protein 43,47) .…”
Section: Discussionmentioning
confidence: 99%
“…For example, benefits of 3 LC-PUFA from fish and fish oil have been observed at different stages of this disease process -including on plasma triglycerides [36][37] (arising from decreased endogenous synthesis and enhanced clearance of triglyceride-rich particles), on the size and the density of lipoprotein particles [38], thrombosis, inflammatory markers [39], blood pressure [29,33], vascular endothelium [30,33,40], proliferation of vascular smooth muscle and growth of atherosclerotic plaque [33,36,41], disorders of cardiac rhythm and sudden cardiac death [16,31,[42][43][44][45]. This review highlights some of the recent findings that demonstrate the effects of 3 LC-PUFA in influencing several key cardio-metabolic parameters, including hypertension, insulin resistance and diabetes in humans.…”
Section: Introductionmentioning
confidence: 99%